(untitled) (The Pakistan Development Review, 1990)
This book deals with an important but relatively little discussed aspect of industrial development in the context of a developing economy. The subject-matter chosen for analysis is that of the efficacy of controls over industry in India. The author provides a detailed and insightful analysis of the issue in its historical context, particularly since India’s independence in 1947. Based on an insider’s experience, the book makes an important contribution to the often neglected field of industrial policy. The central thesis advanced by the author is that the State has played a dominant role in industrial development by way of ownership and/or management of some of the key industries, the granting of industrial incentives, and an elaborate and complicated regulatory system. There have been shifts in emphasis between these three main instruments of state intervention in industrial development over time. Nonetheless, it is argued that currently Indian industry is overregulated, public sector industries are mismanaged, and the economic environment for the working of both private and public sector industries is inimical to their efficient working and growth. The broad approach adopted provides for a discussion of objectives, policy instruments, and the intended and unintended impact of different instruments of state intervention in industrial development. The wide discrepancy between the objectives and the results is shown to be a major failing of the past industrial policies in the context of the Indian development experience.